Meninjau Urgensi Penerapan Purcell Principle pada Pemilihan Umum (Pemilu) di Indonesia - Ibrahim Ghifar Hamadi (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
The absence of limitations on the Constitutional Court to adjudicate court decisions regarding electoral regulations ahead of electoral contests has become a serious issue in Indonesia. Without clear limitations, court decisions have the potential to disrupt the electoral administration process and create uncertainty that could harm the electoral order. Reflecting on Constitutional Court Decision Number 90/PUU-XXI/2023, which regulates the age requirements for presidential and vice-presidential candidates before elections, serves as a stern reminder that the courts should not grant judicial review related to elections as it may give rise to conflicts of interest and tend to favor one party. To address this issue, the application of the Purcell Principle in Indonesia is necessary. The research method used is normative legal research using a legal approach and utilizing secondary data in the form of literature materials, such as legislation, court decisions, books, scholarly articles, and internet sources regarding the Purcell Principle. This study concludes that the application of the Purcell Principle is needed in Indonesia. Considering the concept of the Purcell Principle already applied in the United States, Indonesia must adopt the Purcell Principle to ensure order and legal certainty in the conduct of elections in the country.